Vectorial insulin secretion by pancreatic β-cells - Cortizo, Ana María (1990)
Morphological studies of pancreatic β-cells have suggested the presence of discrete sensory and secretory domains. In the present study we now provide functional evidence by demonstrating polarity of insulin release by HIT-T15 cells. A significant diffusion barrier across a twin chamber culture system was verified in the presence of confluent HIT-T15 cells. When stimulated with sulphonylurea, ionophore or high potassium, insulin was preferentially released into the lower chamber irrespective of whether secretagogues were added to the upper or lower chambers. Vectorial insulin secretion may be a significant determinant of islet hormone paracrine interactions in the maintenance of glucose homeostasis.